Past and present distribution of the Common Myna Acridotheres tristis in Italy: a review (Avocetta, 2020)
Biological invasions represent one of the main causes of the current biodiversity loss. Assessing distribution of invasive species is therefore pivotal to design effective management plans. In this work, we reviewed the current distribution of the Common Myna Acridotheres tristis in Italy. The Myna is recorded as an invasive species in many other countries worldwide. We used citizen-science and online platforms, to obtain a reliable map of the distribution of breeding populations, as very few data have been published on the distribution of this bird in Italy. We found 34 occurrences of the Common Myna in Italy, and breeding has been confirmed in two areas in Campania (Southern Italy), i.e. in the provinces of Salerno and Caserta. To prevent this species to become invasive in Italy, given the current limited distribution of breeding populations, a rapid removal of free-ranging individuals should be recommended in the short-term period.
Keywords: Acridotheres tristis; biological invasions; distribution; invasive alien species; impacts